AN ANALYSIS ON TEACHER’S FEEDBACK IN TEACHING WRITING AT MADRASAH ALIYAH DARUL FATAH TERATAK PADANG - Riyan Hidayat; Vitri Angraini Hardi; Putri Asilestari (Universitas Pahlawan Tuanku Tambusai, 2021)
This research aims to describe the feedback used by the teacher in teaching writing at the tenth-grade students at MA Darul Fatah Islamic Boarding School, Teratak Padang. It was conducted by using descriptive qualitative design. The technique of data collection employed in this research were documentation and interview. This research employed the students’ writing draft as primary data and the result of the English teacher’s interview as secondary data. The findings showed that the teacher used 4 types of feedback; direct feedback, indirect feedback, mixed feedback, and written feedback correction on students’ writing. Mixed feedback is a type of feedback that mostly used on students’ writing. Meanwhile, the feedback given by the teacher in teaching writing at MA Darul Fatah was the written feedback correction on students’ writing. The written feedback is the notes such as a praise, motivation, guidance or information about common mistakes of students during writing. Keywords : Teacher’s Feedback, Teaching Writing, Students’ Writing